Atlas and Farm Directory of Fillmore County, Minnesota (plat book) - Webb Publishing Company (Fillmore County Historical Society, 1915)
Atlas and Farm Directory with complete survey in township plats of Fillmore County Minnesota. Contains plats of all townships with owners names; maps of the State, United States, and World; an outline map of the county showing location of townships, villages, schools, churches, railroads, streams, county roads, wagon roads, cemeteries etc. Compiled from latest data on record. Published by The Farmer; the oldest farm publication in the State; published every Saturday, established in 1882. A Journal of Agriculture, St. Paul, Minnesota.